2023
DOI: 10.2196/42646
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Dynamics of the Social Environment Through Experience Sampling Methods, Passive Sensing, and Egocentric Networks: Scoping Review

Abstract: Background Social interactions are important for well-being, and therefore, researchers are increasingly attempting to capture people’s social environment. Many different disciplines have developed tools to measure the social environment, which can be highly variable over time. The experience sampling method (ESM) is often used in psychology to study the dynamics within a person and the social environment. In addition, passive sensing is often used to capture social behavior via sensors from smartp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…They found that some individual characteristics, such as age and partisanship, are predictive of over-self-reporting on Facebook, but not on Twitter. Recently, Langener et al [54]publishedareviewonthe combined application of passive-measurement methods and daily-life surveys (Experience Sampling Methods; e.g., Csikszentmihalyi and Larson [16]; Trull and Ebner-Priemer [90]) to capture participant's social context. While highlighting the importance of combining these data sources, they conclude that there is a strong need for better-validated measurement methods.…”
Section: Advantages Of Combining Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that some individual characteristics, such as age and partisanship, are predictive of over-self-reporting on Facebook, but not on Twitter. Recently, Langener et al [54]publishedareviewonthe combined application of passive-measurement methods and daily-life surveys (Experience Sampling Methods; e.g., Csikszentmihalyi and Larson [16]; Trull and Ebner-Priemer [90]) to capture participant's social context. While highlighting the importance of combining these data sources, they conclude that there is a strong need for better-validated measurement methods.…”
Section: Advantages Of Combining Data Sourcesmentioning
confidence: 99%
“…Second, there are ethical and methodological issues -such as the external validity of online-behavior for understanding offline behavior (e.g., Jürgens et al [48]). Third, the lack of conceptual and theoretical frameworks incorporating both types of data, such as the processing of data types with different temporal granularity (Langener et al [54]; Stier et al [86]). Despite these challenges, the combination of data sources holds great potential for the joint study of digital social behavior.…”
Section: Advantages Of Combining Data Sourcesmentioning
confidence: 99%
“…Recently, Langener et al. [ 54 ] published a review on the combined application of passive-measurement methods and daily-life surveys (Experience Sampling Methods; e.g., Csikszentmihalyi and Larson [ 16 ]; Trull and Ebner-Priemer [ 90 ]) to capture participant’s social context. While highlighting the importance of combining these data sources, they conclude that there is a strong need for better-validated measurement methods.…”
Section: Advantages Of Combining Data Sourcesmentioning
confidence: 99%
“…Conceptual clarity is critical in all psychological studies because poorly defined concepts make it challenging to build theories and interpret results (Bringmann et al, 2022). Nevertheless, there has been a lack of clarity regarding which construct passive smartphone measures aim to capture (Langener et al, 2023). For example, passive measures like GPS and accelerometer data are frequently used to measure social behavior; however, it is not yet clear which social behaviors these measures capture and how accurately these measures capture the intended construct (Langener et al, 2023; Tsapeli & Musolesi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there has been a lack of clarity regarding which construct passive smartphone measures aim to capture (Langener et al, 2023). For example, passive measures like GPS and accelerometer data are frequently used to measure social behavior; however, it is not yet clear which social behaviors these measures capture and how accurately these measures capture the intended construct (Langener et al, 2023; Tsapeli & Musolesi, 2015). Thus, researchers are advised to carefully consider the meaning of each variable they collect.…”
Section: Introductionmentioning
confidence: 99%